OPEX-risk as a source of CAPEX-bias in monopoly regulation - Gert Brunekreeft; Margarethe Rammerstorfer (Jacobs University Bremen, Bremen Energy Research (BER), 2020)
This paper shows with a formal model that under monopoly regulation, OPEX-risk can be a source for a CAPEX-bias. If OPEX and CAPEX are substitutes, the regulated firm can reduce the risk of the firm and thereby reduce the true cost of capital by rebalancing OPEX and CAPEX. If the allowed rate-of-return on capital is not influenced by the firm's actions, this creates a margin between the allowed rate-ofreturn and the true cost of capital. We examine two remedies: first, fixed-OPEX-CAPEX- share (FOCS) which is a variation of TOTEX-regulation and second, OPEX-mark-up. FOCS internalizes the CAPEX-bias and can be implemented easily. The OPEX-mark-up is effective, but it will be challenging to reach the optimum.
Keywords: K23; L12; L51; L9; 330; Capex-bias; Opex-risk; regulated monopoly